Important notes on parameter estimation of solar photovoltaic cell. (1st October 2019) - Gnetchejo, Patrick Juvet; Ndjakomo Essiane, Salomé; Ele, Pierre; Wamkeue, René; Mbadjoun Wapet, Daniel; Perabi Ngoffe, Steve
Highlights: An sample algorithm is used to check the inaccuracies occurred in the parameters identification of the photovoltaic cell. General Algebraic Modeling System is used to extract the best values of parameters of a PV cell and PV module. Tools are applied to check and extract parameters from single and double diode model. General Algebraic Modeling System is applied to four different case studies. Comparison with recent methods in the literature show the superiority of General Algebraic Modeling System. Abstract: To evaluate the performance of a photovoltaic panel, several parameters must be extracted from the photovoltaic. Among the methods developed to extract photovoltaic parameters from current-voltage (I-V) characteristic curve, metaheuristic algorithms are the most used nowadays. The aim of this paper is to present the inaccuracies occurred in the parameter's identification of the photovoltaic cell using metaheuristic technics published in Energy Conversion and Management. The results presented by different authors do not meet the objective function. To prove it, an algorithm is proposed to check the accuracy of the proposed results; a simple tool, General Algebraic Modeling System is also proposed to extract the best values of parameters of a photovoltaic cell.